Effect of Ca2+ Substitution on the Structure, Microstructure, and Microwave Dielectric Properties of Sr2Al2SiO7 Ceramic. Issue 12 (15th October 2013) - Manu, Kurusaroor Mana; Karthik, Chinnathambi; Ubic, Rick; Sebastian, Mailadil Thomas; Chen, X. M.
<x xml:space="preserve">Abstract</x> The effect of Ca2+ substitution on the structure, microstructure, and microwave dielectric properties of Sr–gehlenite (Sr2Al2SiO7) ceramic has been investigated. The structure and microstructure of Sr2−xCaxAl2SiO7 ceramics were analyzed via X‐ray diffraction (XRD) as well as scanning and transmission electron microscopic techniques. While the end‐members (x = 0 and 2) form isostructural compounds, a highly defective, nonstoichiometric, Ca‐rich secondary phase was observed via bright‐field transmission electron microscopy and energy dispersive X‐ray spectroscopy in compositions corresponding to x = 0.75 and 1.5. The concentration of secondary phase in x = 0.75 is too low to be detected via XRD or scanning electron microscopy. Identical selected‐area electron‐diffraction patterns of the compounds (x = 0, 1, and 2) confirmed that they belong to the space group P<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3zmnbf6g" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />4¯</alternatives>21m (no. 113) with tetragonal crystal symmetry. The porosity‐corrected relative permittivity at microwave frequencies showed a gradual increase with Ca2+ content; however, Ca2+ substitution made only marginal changes to the microwave dielectric properties except in the case of x = 1.5, in which the secondary phase reduced the quality factor considerably. Thermal conductivity decreased with increasing Ca2+ content, and the compounds with defective structures showed the lowest thermal conductivity. All the compounds exhibited low coefficients of linear thermal expansion, with values varying in the range 2.3–3.6 ppm/°C.